EFEKTIVITAS FLASHCARD AUGMENTED REALITY DALAM MENGENALKAN KOSA KATA BAHASA INGGRIS ANAK DI TAMAN KANAK-KANAK BAITURRIDHA 2 LUBUK BUAYA - Mutia Aulia; Rismareni Pransiska; Elise Muryanti; Saridewi (STKIP Subang, 2025)
This research is motivated by the lack of use of learning media in the context of children's introduction to English. This research aims to determine the effectiveness of augmented reality flashcards in introducing English vocabulary to children at Baiturridha 2 Lubuk Buaya Kindergarten. This research uses a quantitative pre-experimental design approach with the One-Group Pretest-Posttest Design type with a purposive sampling technique, namely selecting samples based on certain criteria that are relevant to research needs. Data were analyzed using the Paired Sample T-Test with a significance level of 0.05. The results of the research show that there is significant effectiveness of using augmented reality flashcard media in introducing English vocabulary to young children. This is proven by the increase in the average score from the pretest of 6.10 to 13.40 on the posttest. Apart from that, the results of the Paired Sample T-Test show a significance value (Sig. 2-tailed) of 0.000 < 0.05, so it can be concluded that the use of augmented reality flashcard media is effective in introducing English vocabulary to young children. The conclusion of this research is that the value of d = 5,45 is obtained so that the effectiveness of augmented reality flashcard media is classified as very high.